Фактори економічного розвитку країн в умовах загострення глобальних проблем світової безпеки - Паршина, Олена Анатоліївна; Паршина, Маргарита Юріївна; Чумак, Тетяна Валентинівна (ВД «Гельветика», 2021)
UKR: Аналіз сучасних процесів світової глобалізації засвідчує формування нової багатополярної моделі світового устрою, у рамках якої з’являються нові центри в системі глобальної економіки. Однак динамічний економічний розвиток цих центрів супроводжується формуванням різних політичних та економічних інтересів, унаслідок чого на світовому рівні посилюється нестабільність та з’являються збройні конфлікти. Основна мета статті полягає у визначенні домінантних чинників впливу на економічний розвиток країн, які функціонують в умовах загострення глобальних проблем світової безпеки. У процесі проведення досліджень зазначено активізацію сукупності чинників глобального значення. Із метою визначення домінантних чинників впливу на економічний розвиток країн запропоновано використання когнітивного підходу. Розроблено когнітивну модель економічного розвитку у вигляді орієнтованого графа, вершинами якого є фактори, а дугами – взаємозв’язки між цими факторами. Визначено фактори з домінантним, високим та середнім рівнем впливу. Сформовано основу для розроблення закономірностей та проведення когнітивного моделювання.

ENG: Analysis of modern processes of globalization and geopolitical changes shows the formation of a new multipolar model of the world, in which new centers appear in the global economy. Dynamic economic development is accompanied by the formation of various political and economic interests, resulting in increasing of the global instability and armed conflicts. The duration of armed conflicts significantly affects the macroeconomic and microeconomic indicators, having a negative effect on the processes of global economic development. Increasing of the global instability, resolving wars or armed conflicts are a serious challenge to the world security and building an effective system of the international economic relations. The main purpose of the article is to determine the dominant factors influencing the economic development of countries that operate in the context of exacerbation of the global problems of world security. The activation of a set of the global importance factors in this research has been indicated. Analysis of the dynamic growth process of the countries that are accompanied by growing geopolitical tensions has been carried out. Analysis of the main events in the regions of the world from the point of view of aggravation of global problems of world security has been conducted. The cognitive approach to the structuring information and determination of the dominant factors that are injected into economic development of regions, which function in the conditions of exposure of global problems of world security has been promoted. The cognitive model of the economical development of the countries has been developed. The factors with dominant, high and average levels injected on the economic development of the regions, which function in the conflicts have been determined. Using of the cognitive approach allows to present a multitude of factors that could be added to the economic development of the country. The basis for the definition of regularities and the conduct of the cognitive model has been formed. When carrying out the modeling, testing the development scenarios for economic development has been planned. That allows to develop trends and detailed characteristics of the economic situation and to develop the economic development model.
Factors of Economic Development of Countries in the Condition of Exposure of Global Problems of World Security
О. Паршина: ORCID 0000-0002-7836-0140; М. Паршина: ORCID 0000-0001-9256-1929; Т. Чумак: ORCID 0000-0001-9167-3726
Keywords: глобалізація; економічний розвиток; світова безпека; фактори економічного розвитку; globalization; economic development; world security; factors of economic development; КЕОМ; SOCIAL SCIENCES; SOCIAL SCIENCES::Business and economics